IMPLEMENTASI CRM WEB MOBILE UNTUK EFISIENSI PERENCANAAN PEMBELIAN DAN PENYEDIAAN JASA PT. SEMESTA JARING MEDIA - Setiawan, Agus; Oktapriandi, Sony (LPPM UNIVERSITAS BINA INSAN, 2025)
This article discusses the implementation of a mobile web-based Customer Relationship Management (CRM) system to enhance the efficiency of purchasing planning and service provision at PT. Semesta Jaring Media. In an increasingly competitive business environment, CRM serves as a strategic tool for analyzing customer interactions and managing relevant data to improve service quality and customer satisfaction [1][2]. This research employs a user-centered design approach for system development, resulting in a responsive and user-friendly design [3][4]. Data from the implementation indicates a significant increase in operational efficiency, including reduced information processing time and expedited decision-making [5]. Additionally, the integration of this CRM system contributes to improved customer loyalty through better relationship management [6][7]. The findings from this case study are expected to provide a positive contribution to the development of information technology in the service sector and strengthen the competitive position of PT. Semesta Jaring Media in the market [8][9].